Aplicação de uma sequência didática de ensino usando a teoria dos campos conceituais para o estudo das leis de Kepler no ensino médio - RIBEIRO, Gyulianna Pinheiro (2020)
The work proposed here objectively addresses the concepts referring to Physics about the movement of celestial bodies and their causes based on content - Kepler's Laws, in the light of Vergnaud's Conceptual Field Theory (CFT) (1990), as an instrument for planning together with the Investigative Teaching Sequence (ITS) methodology for the analysis of didactic intervention activities. The research was carried out with students of the 1st grade of high school, at CE Professor Barjonas Lobão, in the city of São Luís - MA, where they were followed all the trajectories of learning the concepts and identifying indications of operational invariants of the CBT, in several potentially favorable situations such as: (1) activities demonstrating the laws; (2) presentation of models; (3) concept maps; (4) lapbook workshop. For the analysis of the situations, the SOLO taxonomy was used, which allows analyzing and classifying the students' level of learning in relation to the concepts presented by them. The objective of this proposal is to obtain through SEI and the psychological theory of the process of conceptualization of the real, to contribute through applied pedagogical situations to a greater acquisition of necessary skills, applied to students, so that they can understand the physical concepts addressed, and the from there, raise the learning process of knowing how to say how to do, as a pedagogical practice being constantly monitored by the teacher. With this, the results showed that it is possible for the teacher, based on the theory and methodology used, to outline teaching-learning strategies, which challenge students to think and seek more challenging and elaborated solutions and explanations for the physical phenomena studied using more significant learning.